1983
DOI: 10.1056/nejm198306023082201
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Fibrinolytic Therapy in Acute Myocardial Infarction

Abstract: We performed a randomized trial comparing intracoronary administration of streptokinase versus dextrose placebo within six hours after the onset of symptoms of acute myocardial infarction in 40 patients. The base-line clinical, hemodynamic, and angiographic findings were similar in the control and streptokinase-treated groups. Reestablishment of flow occurred in 12 of 20 patients treated with streptokinase and in 2 of 20 given placebo (P less than 0.05). Left ventricular function, angiographic ejection fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(34 citation statements)
references
References 20 publications
1
31
2
Order By: Relevance
“…More recently, the Western Washington Intracoronary Streptokinase Trial, 255 a large multicenter, randomized study involving 250 patients, showed a 30-day mortality significantly lower in the SK group than in the controls, although the intervention was delayed up to 12 hours and the rate of reperfusion (68%), similar to that achieved in previous studies utilizing relatively late interventions, 249 was lower than that resulting from earlier infusions. 248 All the 13 control patients who died failed to have reperfusion after catheterization.…”
Section: Thrombolytic Therapysupporting
confidence: 58%
See 1 more Smart Citation
“…More recently, the Western Washington Intracoronary Streptokinase Trial, 255 a large multicenter, randomized study involving 250 patients, showed a 30-day mortality significantly lower in the SK group than in the controls, although the intervention was delayed up to 12 hours and the rate of reperfusion (68%), similar to that achieved in previous studies utilizing relatively late interventions, 249 was lower than that resulting from earlier infusions. 248 All the 13 control patients who died failed to have reperfusion after catheterization.…”
Section: Thrombolytic Therapysupporting
confidence: 58%
“…249 Thrombolytic treatment still showed a trend toward a lower mortality rate than placebo treatment. However, measurements of ventricular function at the time of intervention, after 12 days, and after 5 months did not indicate any advantage from SK infusion.…”
Section: Thrombolytic Therapymentioning
confidence: 98%
“…These agents have in cluded the use of antiarrhythmic drugs, anti coagulants, digoxin, nitrates, platelet-active agents, calcium channel and beta-blockers and lipid-lowering agents. Intense efforts are currently focused on the role of clot lysing agents in improving left ventricular function and long-term survival after acute MI [19,23,24,33,36], Clinical trials and observational studies carried out to date have either questioned the efficacy or noted potentially detrimental effects of some agents such as antiarrhythmic drugs [6,[11][12][13]35] and digoxin [8,25,27], and inconclusive results with regard to others including platelet-active agents [2,3,14,16,17,31 ] and intracoronary or intrave nous nitrates [18,22,33], The most compel ling evidence to date has been gathered from randomized controlled clinical trials that have noted improved survival for patients treated with beta-adrenergic blocking agents after acute MI [1. 4.…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistically significant difference in mortality rates after one year . Several other ICSK studies (Anderson et al, 1983;Khaja et al, 1983;Simoons et al, 1983) with small sample sizes were available but no positive conclusions can be derived from these. Furberg (1984) in an editorial, pooled data from 8 randomized trials of ICSK and concluded that there was an 11 % reduction of mortality in the patients treated with SK when compared to controls.…”
Section: Mortalitymentioning
confidence: 99%